Analysis of Leading Food Crop Commodities In Bulungan District North Kalimantan - Zulhafandi Zulhafandi; Yulianah Yulianah; Nia K Suryana; Khaerunnisa Khaerunnisa (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
The development of the economic and agricultural sectors is important in utilizing resources to increase regional potential in the economic development of a region. Bulungan is a district with great potential in utilizing its regional advantages as an industry-based food center and is currently one of the districts that must be ready to develop and sustain the food of the New Capital City, which is the background for this research to be carried out. This study aims to analyze the leading sectors using the LQ method, trends, and shift shares in food crop commodities in Bulungan Regency. This study uses quantitative data (time series) in the form of data from 2018-2022 (5 years). The data analysis method used is descriptive analysis with a quantitative approach, including Location Quotient (LQ) Analysis, Trend Analysis, and Shift Share Analysis. Based on the LQ analysis results, commodities with an average value of LQ > 1 are rice and corn commodities, which means that Bulungan Regency is a base commodity with potential/superiority. In contrast, peanuts, cassava, and sweet potatoes have an average value of LQ < 1, meaning they are non-base commodities. 1, which means that they are non-base and non-potential commodities in Bulungan Regency as a result of trend analysis to determine the development of rice commodity forecasting in Bulungan Regency in 2023 - 2027. The results of the calculation were obtained using the analysis of the least square method so that the trend equation was obtained as follows: Y = -830.50X + 13,724.20, and it can be known that the results of trend analysis on rice commodities have decreased and have a negative value with an annual decrease of -830.50.